Implementasi Metode MAUT dalam Sistem Pendukung Keputusan Seleksi Penerimaan Stock Keeper Restoran dengan Pembobotan Rank Order Centroid - Abdullah, Mohammad Aldinugroho; Aldisa, Rima Tamara (Forum Kerjasama Pendidikan Tinggi, 2022)
In a restaurant that is running well, of course, it requires the best quality human resources. One of the human resources that is needed by a restaurant is a stock keeper. Stock keeper restoration is needed to ensure that supplies are maintained properly. The selection process for receiving stock keepers is still carried out conventionally so that the selection process is sometimes not appropriate in accepting the best stock keepers. In determining the selection of restaurant stock keepers, there are several criteria, namely work experience, education, ability to operate Microsoft, attitude, communication, psychological test, interview, personal vehicle and age. Because of these problems, a system is needed that can assist in obtaining reliable and targeted recommendations. The application of a decision support system in this study is used by implementing the Multi-Attribute Utility Theory (MAUT) and ROC methods where these methods are very helpful in producing the best weight and preference values ​​from alternative data and criteria so as to get the final result, namely the best restaurant stock keeper recommendations the Alternative A5 with a score of 1,005 on behalf of Lollymoci